2012
DOI: 10.1007/s12602-012-9093-z
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Action of Lactobacilli and Bifidobacteria in Relation to Staphylococcus aureus and Their Influence on the Immune Response in Cases of Intravaginal Staphylococcosis in Mice

Abstract: The antibacterial activity of Lactobacillus casei IMV B-7280, Lact. acidophilus IMV B-7279, Bifidobacterium longum VK1, and B. bifidum VK2 strains or their various compositions in relation to Staphylococcus aureus in vitro and on models of experimental intravaginal staphylococcosis of mice was determined. It was found that under the influence of these strains and their various compositions, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…, ; Lazarenko et al . ). However, the preventive effect of lactobacilli on GBS in animal experimental models was not evidenced up today.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…, ; Lazarenko et al . ). However, the preventive effect of lactobacilli on GBS in animal experimental models was not evidenced up today.…”
Section: Discussionmentioning
confidence: 97%
“…), and can activate the immune system, improving the host's response against urogenital pathogens (Lazarenko et al . ; Wagner and Johnson ). In the present work, the i.va.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results suggest the potential using of probiotics in order to alleviate the occurrence of metabolic diseases by less radical approach comparing with drugs or hormone therapy. We showed that preliminary selected and characterized probiotic strains of Lactobacillus casei IMV B-7280, Bifidobacterium animalis VKL, B. animalis VKB and their various compositions have high ability to balance immune response to infectious diseases [15] and are able to effectively prevent MSG-obesity in rats [16].…”
Section: Introductionmentioning
confidence: 99%
“…It takes place multisynergism of anti-Candida action between PBL and antibiotics (azoles, amphotericin B, nystatin). Taken together, PBL imitate anti-Staphylococcus and anti-Candida activities of probiotic lactobacilli and bifidobacteria [33,34] and can be potentially used for treatment of candidoses and staphylococcoses.…”
Section: Interactions Between Pbl and Gcmentioning
confidence: 99%